PENGETAHUAN IBU HAMIL TENTANG MANFAAT MEDITASI SELAMA KEHAMILAN KLINIK HJ, NANI, S. Keb JALAN NENAS NO 03 KECAMATAN RANTAU UTARA KABUPATEN LABUHANBATU - Nurhayanti; Rani Darma Sakti Tanjung (Media LPPM Sehati, 2022)
Meditation is the process of training the mind to control it and make it more focused. Meditation is also considered to be able to help a person relieve stress and give peace to the heart and mind. This activity can be done in an easy way and in a relatively short time. The benefits of meditation can also be a psychiatric therapy without using chemical drugs that can interfere with pregnancy. Meditation is now widely used as a complementary therapy. So many yoga centers have developed that offer meditation to overcome anxiety in pregnant women. The purpose of this community service is so that pregnant women at Hj Clinic, Nani, S. Keb can understand how to do the benefits of meditation during pregnancy. The method used in this service is counseling and providing brochures about the benefits of meditation during pregnancy. Activities carried out for pregnant women The management in meditation are: preparing tools, opening prayer, doing yoga asanas, starting meditation by doing meditation postures, focusing on breathing during meditation, giving positive affirmations for 10-15 minutes, ending meditation By taking three deep breaths, return to self-awareness, move your fingers and toes, open your eyes slowly and then rub your hands together and then gently rub them over your face until your entire body, closing prayer. The implications after doing meditation for pregnant women are: pregnant women feel calm, comfortable and able to think positively during pregnancy. So it can be concluded that this community service activity has been carried out well. Pregnant women understand the explanation of the benefits of meditation during pregnancy and understand how to do the benefits of meditation Keywords: Knowledge, Pregnant women, benefits of meditation